Mobile health interventions for perinatal and postpartum depression among asian americans: a scoping review - Supriya Rana; Renee Buster (Exploration of Digital Health Technologies, 2026)
Background: Perinatal depression (PD) and postpartum depression (PPD) are leading causes of morbidity in the United States (U.S.). Asian American women, the fastest-growing racial groups in U.S., are disproportionately affected by cultural stigma, language barriers, and limited access to culturally responsive healthcare. This review examines the current methods, evidence gaps, and opportunities to address perinatal and PPD through mobile health (mHealth) applications among Asian American women. Methods: A scoping review was conducted using PubMed, EBSCOhost, Google Scholar searches following the principles of systematic and rapid review methodology. Articles were included if they addressed Asian American women with PD or PPD, focused on mHealth or telehealth interventions, and peer-reviewed publications from last ten years. A total of 246 articles were identified, from which 25 studies were selected for inclusion. Data were synthesized thematically across six domains. Results: The sample included observational (24%), qualitative (16%), pilot (12%), RCTs (12%), reviews (24%), protocols (8%), and mixed (4%); Edinburgh Postnatal Depression Scale (EPDS) was most frequently used (68%). mHealth tools with hybrid approaches were widely used regardless of location and systemic barriers. Mindfulness and cognitive behavioral therapy (CBT)-based interventions were effective in reducing depressive symptoms, improving maternal self-efficacy, and enhancing psychosocial outcomes. However, engagement was lower among women with severe depressive symptoms, and mental illness stigmatization limited access to digital tools. Key motivators for uptake included connectivity, feasibility, and adaptability. Discussion: mHealth interventions demonstrate considerable potential to improve depressive symptoms during perinatal and postpartum periods. However, their implementation and evaluation among Asian American women remain limited. Future interventions should prioritize culturally and linguistically tailored digital platforms, integrate peer and professional support, and align with existing maternal healthcare systems to improve accessibility, engagement, and equity while addressing persistent disparities in maternal mental health.